(untitled) (Journal of Media, Journalism & Mass Communication, 2025)
Although it is claimed that the concept of existence has no definition, many different definitions and interpretations have been made by philosophers who have pondered this field throughout history. While most ancient philosophers and scientists were interested in the problem of what existence is and what it is, the essence (origin) of existence was also a matter of curiosity. According to some, the first being or the essence of being was air, water, and fire. According to the others, they are concepts such as ‘One, logos, idea, substance, cogito, perception, monad, object, self, soul, will’ and power. While the problem of knowledge of existence (ontology) goes through many philosophical stages and focuses on it as a research topic, it can be seen that in later stages this focus shifts to what knowledge is and what it is (epistemology). The method of reaching true (absolute) knowledge has varied from age to age. While scientific and transmitted knowledge was popular in ancient times to reach true knowledge, positive science was used as a reference in reaching absolute knowledge in modern and post-modern ages. This scientific method, which centers on experiment and observation, has been accompanied by technical technological developments. While mass media, and in this context, cinema/television based on visuality, gained great momentum after the 19th century, the first impression created by the train of the Lumiere brothers coming towards people was replaced by panic and fear. Therefore, the truth between visuality and reality has been questioned. What is intended to be done in this study is to try to understand the relationship between existence, image, reality, and effect.